Cement leakage during vertebroplasty: comparison between intact and wall disruption in spinal metastases. (May 2023) - Gravel, Guillaume; Roussel, Alexandre; Guth, Axel; Mellot, François
Background: Percutaneous vertebroplasty (PVP) is an effective measure for painful metastases or impending pathological fractures of the spine with cement leakages being the most frequent complication. Posterior extrusion of cement into the spinal canal may result in neurological symptoms and deficits. Purpose: To compare the occurrence of intraspinal canal cement leakage between vertebrae with posterior wall disruption and vertebrae without posterior wall disruption. Material and Methods: A single-center retrospective study was conducted of all PVP for spine metastases between June 2020 and November 2021. All leaks were analyzed by a postprocedural computed tomography scan or cone-beam computed tomography. Results: A total of 77 patients with 143 vertebrae treated by PVP were included. Posterior wall disruption was observed in 64 (44.8%) vertebrae while 79 (55.2%) had a complete posterior wall. Spinal canal cement leakage occurred in 36 (25.2%) vertebrae and was comparable in both groups, occurring in 16 (25.0%) vertebrae with posterior wall disruption and 20 (25.3%) vertebrae without posterior wall disruption ( P = 1). No risk factors for spinal canal leakage were found in the univariate and multivariate analyses. One spinal leak was symptomatic with intercostal neuralgia. Conclusion: Our results suggest that an incomplete vertebral posterior wall does not increase the rate of spinal canal cement leakage during PVP.